MODEL DINAMIK PENGENDALIAN PENCEMARAN AIR KALI SURABAYA - Suwari, Suwari; Riani, Etty; Pramudya, Bambang; Djuwita, Ita (Bumi Lestari; Vol 11 No 2 (2011), 2011)
The Surabaya River plays an important role as water supply of the Surabaya PDAM, irrigation, industry, transportation, and means of recreation. However, domestic, industrial, and agricultural waste that were discharged into the river stream polluted the Surabaya River and decreased the carrying capacity and assimilative capacity. Therefore, effort to monitor and control the Surabaya River water pollution need to be well organized and implemented. The aim of the research is to develop a model of water pollution control on Surabaya River region. The research was carried out based on field survey, in situ and laboratory sample examination, questionnaire, and expert judgment. Pollution control model developed in this study was built into three sub-models, namely: (1) ecology sub-model, (2) social sub-model, and (3) economy sub-model using powersim constructor 2.5 version. Pollution control scenarios were developed using prospective analysis. The results of water pollution parameters such as TSS, DO, BOD, COD, N-NO2, and the level of mercury (Hg) were higher than the allowable class 1 standard. The sources of Surabaya River pollution mainly are domestic and industrial waste with total load of BOD, COD, and TSS are 55.49, 132.58, and 210.13 ton/day, respectively. According to water quality status, the Surabaya River is categorized as heavy polluted and the loading pollution need to be decreased. By using prospective analysis, there were five important factors that affect the future of the Surabaya River water pollution control, i.e.: (1) population growth and community awareness, (2) community perception, (3) implementation of regulations, (4) commitment/local government support, and (5) system and institutional capacity. There are three development scenarios, that are pessimistic, moderate and optimistic. The moderate and optimistic scenario are the realistic scenarios that occur in the future for Surabaya River water pollution control in considering of ecology, social and economy aspects.
Keywords: Dynamic model, pollution control, prospective analysis, Surabaya River